PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN JASA PENGIRIMAN PT. AGILITY INTERNATIONAL - Dimas Panji Fikri Pratama; Nino Nopriandi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The research aimed to analyze the influence of service quality and company image on the customer service delivery loyality of PT. Agility International. Metode analys was taken using regression of simple and multiple linier analysis. The findings of this research indicated that Service quality has positif and significant with customer Loyality, Corporate Image has positive and significant with customer loyalty, service quality and corporate image has positive and significant with customer loyalty in PT. Agility International.